The impact of firm size on the relationship between leverage and firm performance: evidence from Saudi Arabia - Nouf Alabdulkarim; Lakshmi Kalyanaraman; Hanan Alhussayen (Humanities & Social Sciences Communications)
Abstract Capital structure and its relationship with firm performance is one of the most debatable topics in corporate finance among both scholars and policy-makers. Using a panel threshold regression model, this study investigates the impact of firm size on the nonlinear relationship between the leverage and performance of Saudi listed firms from 2010 to 2019. The results reveal that firm size is critical in determining the nonlinear relationship between leverage and firm performance. A single threshold level divides the sample into two regimes of small and large firms. Leverage negatively affects performance in both regimes with different debt maturities. However, the negative impact is more pronounced among small firms, especially when long-term debt is employed. This study adds to the evolving literature because the unique setting of the Saudi market is characterized by its illiquid and underdeveloped bond market. Additionally, Saudi firms are not subject to income tax; instead, they are subject to zakat, which is levied at 2.5%. These characteristics impact the relationship between leverage and Saudi firm performance at different firm sizes. This study is important for financial managers, regulators, researchers, and investors to understand how leverage with different maturities affects performance and the role of firm size in this relationship.